Interactions of nano-oxides with low-molecular-weight organic acids in a contaminated soil - Vítková, Martina; Komárek, Michael; Tejnecký, Václav; Šillerová, Hana (Journal of hazardous materials, 2015)
Various low-molecular-weight organic acids (LMWOAs) play an important role in the mobilisation of contaminants and their subsequent uptake by plants. Nano-maghemite (NM) and an amorphous Mn oxide (AMO) were investigated for their stabilisation potential under simulated rhizosphere conditions in terms of their use during chemical stabilisation and aided phytostabilisation of metal(loid)s in contaminated soils. In order to understand the reactivity of these potential sorbents of contaminants in soils and subsequent mobility of metal(loid)s, a set of time-dependent batch leaching experiments was performed using a mix of acetic, lactic, citric, malic and formic acids simulating root exudates. Despite being relatively unstable under given conditions, the AMO proved to be an efficient amendment for rapid stabilisation of both metals and As compared to NM. Generally, low pH (∼ 4) and the presence of citrate complexes resulted in higher mobility of metals in the non- and NM-amended soil. In contrast, the presence of AMO in the soil accelerated the neutralisation reactions related to pH increase and (co-) precipitation of secondary Fe/Mn/Al oxyhydroxides. Mineralogical transformations of the AMO showed to be crucial for contaminant immobilisation.
Keywords: Metals; kyseliny karboxylové; Molecular Weight; Manganese Compounds; oxidy; látky znečišťující půdu; kovy; molekulová hmotnost; Oxides; sloučeniny manganu; Ferric Compounds; Arsenic; Nano-oxides; Soil Pollutants; Organic acids; železité sloučeniny; Carboxylic Acids; Contaminated soil; arsen; Metal Nanoparticles; kovové nanočástice